Cancer Fighting SiRNA-RRM2 Loaded Nanorobots - Sharma, Arjun; Kumar, Pravir; Ambasta, Rashmi K. (Pharmaceutical Nanotechnology, 2020)
Background: Silencing of several genes is critical for cancer therapy. These genes may be apoptotic gene, cell proliferation gene, DNA synthesis gene, etc. The two subunits of Ribonucleotide Reductase (RR), RRM1 and RRM2, are critical for DNA synthesis. Hence, targeting the blockage of DNA synthesis at tumor site can be a smart mode of cancer therapy. Specific targeting of blockage of RRM2 is done effectively by SiRNA. The drawbacks of siRNA delivery in the body include the poor uptake by all kinds of cells, questionable stability under physiological condition, non-target effect and ability to trigger the immune response. These obstacles may be overcome by target delivery of siRNA at the tumor site. This review presents a holistic overview regarding the role of RRM2 in controlling cancer progression. The nanoparticles are more effective due to specific characteristics like cell membrane penetration capacity, less toxicity, etc. RRM2 have been found to be elevated in different types of cancer and identified as the prognostic and predictive marker of the disease. Reductase RRM1 and RRM2 regulate the protein and gene expression of E2F, which is critical for protein expression and progression of cell cycle and cancer. The knockdown of RRM2 leads to apoptosis via Bcl2 in cancer. Both Bcl2 and E2F are critical in the progression of cancer, hence a gene that can affect both in regulating DNA replication is essential for cancer therapy. Aim: The aim of the review is to identify the related gene whose silencing may inhibit cancer progression. Conclusion: In this review, we illuminate the critical link between RRM-E2F, RRM-Bcl2, RRM-HDAC for the therapy of cancer. Altogether, this review presents an overview of all types of SiRNA targeted for cancer therapy with special emphasis on RRM2 for controlling the tumor progression.
Keywords: RRM2